Optimizing Fairy Tales in Cooperative Integrated Reading and Composition (CIRC) Learning for Elementary Schools - Made Aryawan Adijaya; Erika Wahyu Dianti (Universitas Pendidikan Ganesha, 2024)
Primary school students' reading skills are often low because reading is considered a less enjoyable activity. This study aims to analyze the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by fairy tales in improving the reading skills of elementary school students. This study is pseudo-experimental research with a non-equivalent post-test only control group design. The research population consisted of 98 elementary school students, with a sample of 43 students selected using random sampling techniques. The instrument used in this study is a reading skill test. The data were analyzed using inferential statistical analysis, specifically t-tests. The results showed that there was a significant difference in reading skills between the group of students who followed the CIRC learning model assisted by fairy tales and the group that participated in conventional learning. It was concluded that the CIRC learning model assisted by fairy tales had a positive influence on the improvement of reading skills of elementary school students. The implications of this study show the importance of implementing innovative learning strategies to improve students' reading skills.